Novel class 1 Integrons and sequence types in VIM-2 and VIM-11-producing clinical strains of Enterobacter cloacae - De Belder, Denise (2017)
Fil: De Belder, Denise. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio Antimicrobianos; Argentina.